Analisis Konjoin Dan Metode Kendall’s W Tentang Preferensi Mahasiswa Jurusan Matematika Fmipa Unp Dalam Memilih Berbelanja Online - Amelia, Chairani; Arnellis, Arnellis (UNIVERSITAS NEGERI PADANG, 2024)
Online shopping is one of the processes of buying and selling goods, services and others online without meeting with sellers and buyers who provide various human needs easily. This study aims to find out how the attribute level combination of the students' liking level and the alignment of the attributes used in the study is carried out. The results in this study indicate that the combination of levels that students prefer most in choosing to shop online are products with good quality, low prices, promotions with discounts and free shipping, satisfactory service and a good reputation. The most important attribute for students of the Mathematics Department of FIMPA UNP in choosing to shop online is the price attribute because it has a very high level of relativity of 46.16%. In the Kendall's W method, it can be seen that there is harmony between the assessments of the respondents and the 5 attributes studied. This is indicated by the statistical value that is greater than the statistical value of the table, namely 61.79824 > 9.488.